Establishment of biochemical genetic markers techniques for Shorea spp.- tropical forest tree species - Sudarmonowati, E.; Hartarti, N.S.; Siregar, U.J. (1997)
Two types of materials, six compositions of extractions buffer and three electrophoretic buffer system were studied to establish optimum procedures for obtaining good resolution of 14 enzyme systems in 12 species of Shorea which belongs to the family of Dipterocarpaceace. Thirteen (13) enzyme systems could be detected in S.seminis and S.parvifolia, 10 of that in S. laevis, S.leprosula, S.selanica, S.aquminata, S.gibbosa, S.palembanica, and S.pauciflora, 7 of that in S.paquetiana and 4 of that in S.johorensis. The use of W extraction buffer in combination with the use of MC electrophoretic buffer systems led to the best results of using twigs were almost the same as leaves, better resolution of certain enzyme system such as PER, PGI, SDH, and MDH was obtained from leaves. Results obtained from this study would benefit further study on various aspects such as genetic diversity assessment of Shorea species and genetic improvement.